Enhanced solubility, permeability, and tabletability of nicorandil by salt and cocrystal formation - Mannava, M. K. Chaitanya; Gunnam, Anilkumar; Lodagekar, Anurag; Shastri, Nalini R; Nangia, Ashwini K; Solomon, K. Anand (CrystEngComm, 2021)
Cocrystallization is a rational selection crystal engineering approach for the development of novel solid forms with enhanced physicochemical and mechanical properties. Nicorandil (NCR) is a niacinamide vitamin derivative used to treat angina pectoris. A binary solid form screen of NCR with homologous dicarboxylic acids afforded NCR-oxalic acid (NCR-OA, 1 : 1), NCR-fumaric acid (NCR-FA, 1 : 1), NCR-succinic acid (NCR-SA, 1 : 1), and NCR-suberic acid (NCR-SBA, 1 : 0.5). The binary solids were characterized by powder X-ray diffraction, IR and NMR spectroscopy, and DSC. NCR-FA and NCR-SBA were crystallized by slow evaporation from chloroform and toluene solvents, respectively. Single crystal X-ray diffraction confirmed that NCR-FA is a molecular salt, while NCR-SBA is a neutral cocrystal. NCR and the FA anion are connected via the robust carboxylate pyridinium synthon, whereas in the NCR-SBA cocrystal, the components associate via the carboxylic acid pyridine synthon. The phase stability, solubility, dissolution rate, diffusion rate and tabletability studies have demonstrated that the binary solids exhibit improved physical and mechanical properties compared to the NCR drug. Specifically, the NCR-FA salt and NCR-SBA cocrystal have higher solubility, dissolution rate, and hardness at lower pressures, making the formulation suitable for tablet compression. Cocrystallization is a rational selection crystal engineering approach for the development of novel solid forms with enhanced physicochemical and mechanical properties.